2018
DOI: 10.1177/0144598717739394
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mechanisms and distribution characteristics of overpressures in the Paleogene reservoirs of the Bohai Bay Basin, East China

Abstract: The Bohai Bay region is a primary accumulation area of oil and gas in offshore China, in which overpressure commonly occurs in the Paleogene strata; the analysis on distribution characteristics and genetic mechanisms of the overpressure would provide geologic evidences for making plans of well drilling and logging as well as oil and gas exploitation; additionally, it could lay the geological foundation for studying how overpressure controlled hydrocarbon accumulation. Based on research, the overpressure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, the Laotieshan Channel, which is located in the northern part of the Bohai Strait and has a maximum depth of 86 m, has neither Holocene sediments nor Late Pleistocene sediments due to strong tidal erosion (up to 250 cm s −1 ) (Liu et al, 1998). In addition, the Bohai Sea is the largest offshore crude oil/gas development base in China, where hydrocarbon-related overpressure commonly occurs in the Paleogene strata (Xu et al, 2018) and oil/gas leakages have been previously observed .…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Laotieshan Channel, which is located in the northern part of the Bohai Strait and has a maximum depth of 86 m, has neither Holocene sediments nor Late Pleistocene sediments due to strong tidal erosion (up to 250 cm s −1 ) (Liu et al, 1998). In addition, the Bohai Sea is the largest offshore crude oil/gas development base in China, where hydrocarbon-related overpressure commonly occurs in the Paleogene strata (Xu et al, 2018) and oil/gas leakages have been previously observed .…”
Section: Study Areamentioning
confidence: 99%
“…The erosional character of the seabed means that it cannot host methanogenic processes due to an absence of sedimentary organic carbon. Therefore, the high [CH 4 ] values in the water column were probably contributed to natural release of CH 4 due to fault activities related to hydrocarbon-generation sag (Xu et al, 2018).…”
Section: Type Ii: Natural Seeps At the Deep Laotieshan Channelmentioning
confidence: 99%